Determinan Capital Buffer Pada Industri Perbankan Di Indonesia - Agustuty, Lasty; Ruslan, Andi (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2019)
This study aims to analyze the factors that influence capital buffers in the banking industry in Indonesia. Research variables include bank size, liquidity, credit risk, efficiency and profitability as independent variables and capital buffers as the dependent variable. The method used in this study is quantitative research. This research was conducted at public banks on the Indonesia Stock Exchange category BOOK 3 and BOOK 4, with the 2014-2018 research period using multiple linear regression analysis techniques. The results showed that the size of the company did not have a significant effect on capital buffer, while liquidity, credit risk, efficiency and profitability had a significant effect on capital buffer.